The interaction between acetylation and serine-574 phosphorylation regulates the apoptotic function of FOXO3 - Li, Z (Oncogene, 2016)
The multispecific transcription factor and tumor suppressor FOXO3 is an important mediator of apoptosis, but the mechanisms that control its proapoptotic function are poorly understood. There has long been evidence that acetylation promotes FOXO3-driven apoptosis and recently a specific JNK (c-Jun N-terminal kinase)-dependent S574 phosphorylated form (p-FOXO3) has been shown to be specifically apoptotic. This study examined whether acetylation and S574 phosphorylation act independently or in concert to regulate the apoptotic function of FOXO3. We observed that both sirtuins 1 and 7 (SIRT1 and SIRT7) are able to deacetylate FOXO3 in vitro and in vivo, and that lipopolysaccharide (LPS) treatment of THP-1 monocytes induced a rapid increase of FOXO3 acetylation, partly by suppression of SIRT1 and SIRT7. Acetylation was required for S574 phosphorylation and cellular apoptosis. Deacetylation of FOXO3 by SIRT activation or SIRT1 or SIRT7 overexpression prevented its S574 phosphorylation and blocked apoptosis in response to LPS. We also found that acetylated FOXO3 preferentially bound JNK1, and a mutant FOXO3 lacking four known acetylation sites (K242, 259, 290 and 569R) abolished JNK1 binding and failed to induce apoptosis. This interplay of acetylation and phosphorylation also regulated cell death in primary human peripheral blood monocytes (PBMs). PBMs isolated from alcoholic hepatitis patients had high expression of SIRT1 and SIRT7 and failed to induce p-FOXO3 and apoptosis in response to LPS. PBMs from healthy controls had lower SIRT1 and SIRT7 and readily formed p-FOXO3 and underwent apoptosis when similarly treated. These results reveal that acetylation is permissive for generation of the apoptotic form of FOXO3 and the activity of SIRT1 and particularly SIRT7 regulate this process in vivo, allowing control of monocyte apoptosis in response to LPS.